Field Experiment Research of the Polycystic Aeration Bolt: Model Design and Anchorage Mechanism - Wen Xiang Peng; Ming Kai Xu; Yi Fan Chen; Zheng Hao Chen; Zhuo Yang (Advances in Civil Engineering)
As a new type of bolt, the polycystic aeration bolt has a broad application prospect in soft soil area; however, its design and production are still in the stage of constant exploration and improvement. From the perspective of bolt material and engineering cost, the important components of the polycystic aeration bolt were analyzed by combination with the existing bolt models, and a new structural design scheme of a kind of polycystic aeration bolt which can be used in practical engineering was presented in this paper. Then, the stress and failure mode of this bolt were discussed, and the theoretical equation of the bearing capacity was derived by using the elastic-plastic theory. In addition, the assembly and fabrication technology of this bolt in practical foundation pit engineering was described in detail. Finally, the field pull-out test of the polycystic aeration bolt was carried out, and the test results were compared with those of the conventional grouting bolt, which indicated that this new bolt has a greater advantage in bearing capacity than the conventional grouting bolt, verifying the feasibility of the structural design scheme of the polycystic aeration bolt proposed in this paper.